Rotula aquatica Lour. mitigates oxidative stress and inflammation in acute pyelonephritic rats. (2nd January 2022) - Vysakh, A.; Jayesh, Kuriakose; Jisha, Ninan; Vijeesh, V.; Midhun, Sebastian Jose; Jyothis, Mathew; Latha, M. S.
Abstract: The current study evaluates the efficacy of methanolic extract of Rotula aquatica Lour. (MERA) against inflammatory changes associated with acute pyelonephritis. The antioxidant enzymes such as SOD, CAT, GPx, GR and oxidative stress markers like GSH content, malondialdehyde (MDA) level, nitrate level, reactive oxygen species (ROS) level and renal toxicity markers were evaluated in this study. The mRNA level expression of Toll-like receptor 4 (TLR-4), nuclear transcription factor kappa B (NF-κB), tumour necrosis factor-alpha (TNF-α), interleukin-6 (IL-6) and Tamm Horsfall protein (THP) were studied by RT-PCR analysis. The oral administration of MERA increases the antioxidant enzyme status in pyelonephritis rat. The elevated levels of oxidative stress markers in pyelonephritic rats were ameliorated by the administration of MERA at 100 mg/kg and 200 mg/kg bwt of the rat. The mRNA level expression of major genes were restored to normal level by MERA.